FAMILY ECONOMICS EDUCATION, LIFESTYLE, AND INDIVIDUAL MODERNITY AS PREDICTORS OF ECONOMIC LITERACY IN THE CONTEXT OF ECONOMICS LEARNING IN SENIOR HIGH SCHOOLS - Yuni Mariani Manik; Sulasmi Sulasmi; Aan Ikhsananto; Yustirania Septiani (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Consumptive behavior among adolescents has become an increasing concern, as purchasing decisions are often driven more by lifestyle and modernity than by actual needs. However, the mechanism through which family economics education, lifestyle, and individual modernity influence consumptive behavior, particularly through economic literacy, remains unclear. This study aims to examine whether economic literacy mediates the effects of family economics education, lifestyle, and individual modernity on consumptive behavior among senior high school students. A quantitative approach was employed using structural equation modeling (SEM), with data collected through questionnaires and economic literacy tests administered to students selected via proportional random sampling. The results indicate that family economics education has a significant negative effect on consumptive behavior, whereas lifestyle and individual modernity do not. Individual modernity positively influences economic literacy, whereas family economics education and lifestyle do not. Furthermore, economic literacy does not significantly affect consumptive behavior and does not mediate the relationships among the variables. These findings suggest that enhancing economic literacy alone is insufficient to reduce consumptive behavior, highlighting the need for experiential learning approaches that foster rational consumption habits.